The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1111/j.1440-1681.1996.tb02594.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Role of the Lamina Terminalis in the Regulation of Cardiovascular and Body Fluid Homeostasis

Abstract: 1. Cardiovascular and body fluid homeostasis depends upon the activation and co-ordination of reflexes and behavioural responses. In order to accomplish this, the brain receives and processes both neural and chemical input. Once in the brain, information from sources signalling the status of the cardiovascular system and body fluid balance travels, and is integrated, throughout a widely distributed neural network. Recent studies using neuroanatomical and functional techniques have identified several key areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
135
0
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(141 citation statements)
references
References 47 publications
3
135
0
3
Order By: Relevance
“…Previous studies strongly indicate that the MnPO plays a pivotal role in autonomic, neuroendocrine, and behavioral responses to body fluid homeostatic challenges (Johnson and Loewy, 1990;Johnson et al, 1996). The present findings along with our previous study (Stocker and Toney, 2005) demonstrate that MnPO-PVH neurons integrate multiple signals including circulating ANG II, osmotic, baroreceptor, and visceral information arising from vagal afferent fibers.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Previous studies strongly indicate that the MnPO plays a pivotal role in autonomic, neuroendocrine, and behavioral responses to body fluid homeostatic challenges (Johnson and Loewy, 1990;Johnson et al, 1996). The present findings along with our previous study (Stocker and Toney, 2005) demonstrate that MnPO-PVH neurons integrate multiple signals including circulating ANG II, osmotic, baroreceptor, and visceral information arising from vagal afferent fibers.…”
Section: Discussionsupporting
confidence: 83%
“…Anatomical and functional studies suggest the MnPO serves as a forebrain integration site for both humoral and visceral afferent information (Johnson and Loewy, 1990;Johnson et al, 1996). In this regard, our laboratory (Stocker and Toney, 2005) and others (Knuepfer et al, 1985;McAllen et al, 1990;Tanaka et al, 1993;Tanaka et al, 1995;Aradachi et al, 1996) have shown that MnPO neurons are responsive to changes in plasma osmolality, circulating ANG II, and/or changes in ABP.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…ANG II produced in response to these physiological conditions activates ANG II receptors in the subfornical organ and organum vasculosum laminae terminalis (41) and thereby promotes release of neurohypophyseal hormones. Similar to these effects observed during hypovolemia, NO also modulates hormone secretion in response to ANG II, such that when administered in conjunction with ANG II, L-NAME enhances oxytocin, but not vasopressin secretion (Figure 2E,F).…”
Section: Stimulated Conditionmentioning
confidence: 99%
“…It is thought that the active peptides angiotensin II, III, or IV may have roles within the brain in functions as diverse as the regulation of cardiovascular and fluid homeostasis (2,3,11,19,35,40,41,46), reproduction (15), thermoregulation (28), memory (49), cognition, emotional responses to stress and anxiety, cerebral blood flow regulation, and brain developmental processes (39). However, some studies have questioned whether angiotensin is a neuropeptide because of its very low abundance in brain (23) and have proposed that an alternative endogenous ligand may act on angiotensin receptors in the brain (6).…”
mentioning
confidence: 99%